New opportunities in the therapy of steroid-specific dermatosis - combination of topical glucocorticosteroid with urinium - N. N. Filimonkova; M. S. Kolbina (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
External therapy with topical steroids is used for a long time. To date topical glucocorticosteroids (TGCS) are in the leading position in dermatology among all medicines for external therapy. TGCS as a powerful tool of pathogenic action can rapidly reduce or decrease inflammatory changes in the skin and eliminate subjective symptoms of dermatoses (itching, burning). their positive effect lead to the rehabilitation of working ability and daily living activity, positively affect the psychoemotional state and significantly improve the patient's quality of life. Urea in dermatology has been used for a very long time, as it softens the skin, reduces its dryness and eliminates peeling. In recent decades interest in this compound has intensified after a formation of an idea about natural moisturizing factor (NMF) - a complex of substances (which includes urea) being a part of the intercellular matrix of the epidermis and capable of retaining the water in the epithelial layer of the skin necessary for its normal functioning. The article presents modern literature data on the reasoning of the inclusion of a combination of topical glucocorticosteroids with urea in a complex therapy of steroid-responsive dermatoses.